A coupled FDM/FEM model for the continuous casting process. (4th August 2014) - Funk, G.; Boehmer, J.R.; Fett, F.N.
A coupled mathematical model has been developed to investigate the solidification and further cooling, and the formation of thermal stresses, which cause quality defects like internal or surface cracks. The aim is to get a better understanding of the continuous casting process in order to contribute to an increase in productivity while keeping a required quality level, or improving product quality. For the simulation of mass transport, solidification and/or remelting, and heat transfer, a finite difference method is applied; for the calculation of the thermo–mechanical stresses and strains the ADINA program is used. Because the strand shrinkage within the mould determines the temperature field via the cooling conditions, both thermal and stress analysis have to be coupled to consider feedback. Emphasis is placed on the highly nonlinear material behaviour at temperatures near the solidification temperature as well as on the three–dimensional and transient contact between strand and mould. The reliability of the solutions depends on the discretisation and element configuration chosen. Depending on the problem formulation a relatively simple plane strain formulation or a fully 3D stress formulation is used. The alternative possibilities of different grids and/or different material models are discussed with respect to accuracy and CPU–time.